Comparison and prediction of artefact severity due to total hip replacement in 1.5 T versus 3 T MRI of the prostate. Issue 144 (November 2021) - Boschheidgen, M.; Ullrich, T.; Blondin, D.; Ziayee, F.; Kasprowski, L.; Ljimani, A.; Arsov, C.; Albers, P.; Antoch, G.; Schimmöller, L.
Abstract: Purpose: To evaluate image quality and diagnostic value of multiparametric prostate MRI (mpMRI) in patients with total hip replacement (THR) at 1.5 and 3 Tesla. Methods: In this retrospective multicenter cohort study patients with uni- or bilateral THR and 1.5 T or 3 T mpMRI were included. Seventy consecutive, standard-of-care examinations per field strength were evaluated regarding their diagnostic value. The overall diagnostic value and prostate imaging quality score (PI-QUAL) were assessed. Artifact severity in the localizer and mpMRI sequences (T2w, DWI, DCE) was scored on a 3-point scale. Correlation between diagnostic value and artifacts was analysed. Moreover, a subgroup analysis focussed on image quality at different 3 T scanner generations. Results: 140 consecutive patients (mean age 72, median PSA value 8.3 ng/ml) were included. When comparing 1.5 T to 3 T examinations, no significant differences were observed regarding the artifact severity of DWI and the localizer and the overall diagnostic value of the images. There was a strong correlation between the diagnostic value, PI-QUAL score, and artifact severity in the localizer and DWI. T2w and DCE sequences showed overall low artifacts. Significant improvement in image quality for 3 T at the latest scanner generation was observed, especially for DWI (p < 0.03). Conclusions: MpMRI of patients with THR can be conducted at both field strengths without significant differences in artifacts. The localizer might be useful as an early forecasting feature for diagnostic value and particularly for contrast medium application decision. Patients with THR could benefit from technically advanced scanner generation and rs/ptx-EPI DWI sequences.